Ecological and socio-economic assessment of Mopane woodland in the Mahel area in Maputo Province, Mozambique - Foloma, Marcelino Caetano Semo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScConsEcol)--University of Stellenbosch, 2004.